2008
DOI: 10.1113/jphysiol.2007.147959
|View full text |Cite
|
Sign up to set email alerts
|

The calcium channel α2/δ1 subunit is involved in extracellular signalling

Abstract: The α2/δ1 subunit forms part of the dihydropyridine receptor, an essential protein complex for excitation-contraction (EC) coupling in skeletal muscle. Because of the lack of a viable knock-out animal, little is known regarding the role of the α2/δ1 subunit in EC coupling or in other cell functions. Interestingly, the α2/δ1 appears before the α1 subunit in development and contains extracellular conserved domains known to be important in cell signalling and inter-protein interactions. These facts raise the poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 48 publications
(64 reference statements)
4
39
0
Order By: Relevance
“…The discrepancy in subunit levels has been demonstrated both at the mRNA (38) and the protein levels (23), suggesting that ␣2/␦1 may have a role in skeletal muscle independent from the DHPR complex. In agreement with those results, we have found that the ␣2/␦1 subunit localizes at the ends of cells with little or no association with ␣ 1 1.1 subunits in myotubes after 2 days of induction of fusion and differentiation (15). With longer times in differentiation medium, the localization of ␣2/␦1 gradually becomes homogeneous until it colocalizes almost completely with ␣ 1 1.1.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…The discrepancy in subunit levels has been demonstrated both at the mRNA (38) and the protein levels (23), suggesting that ␣2/␦1 may have a role in skeletal muscle independent from the DHPR complex. In agreement with those results, we have found that the ␣2/␦1 subunit localizes at the ends of cells with little or no association with ␣ 1 1.1 subunits in myotubes after 2 days of induction of fusion and differentiation (15). With longer times in differentiation medium, the localization of ␣2/␦1 gradually becomes homogeneous until it colocalizes almost completely with ␣ 1 1.1.…”
supporting
confidence: 76%
“…The association of ␣2/␦1 and ATP5b occurs at both the plasma membrane and in intracellular membranes, as demonstrated by protein labeling with biotin and antibodies, and FRET analysis. We have previously shown that the ␣2/␦1 subunit does not always colocalize with the ␣ 1 1.1 subunit and that it is involved in attachment and migration of myoblasts (15). Thus we hypothesized that the ␣2/␦1 subunit may be interacting with other cellular components different from DHPRs early during development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Double immunofluorescence staining was processed as described previously [25,26]. The sections mounted in gelatin-coated slides were incubated overnight with the following primary antibodies: rabbit polyclonal anti-MOR (1:1000) (gift from S. Schulz and V. Höllt, Magdeburg, Germany) [4] alone or in combination with (a) mouse monoclonal antidihydropyridine receptor (ɑ2 subunit) (1:1000) to identify the voltage-gated L-type Ca 2+ channel (anti-Ca v 1.2) (SIGMA ® , Missouri, USA) [27][28][29], (b) mouse monoclonal anti-Inositol-1,4,5-trisphosphate receptor type III (1:600) to identify ryanodine receptors (RyR) of the sarcoplasmatic reticulum (BD Biosciences ® , Europe) [30,31], or (c) rat anti-mitochondrium marker MTC02 (1:300) to identify mitochondrial structures (Thermo Scientific) [32]. The rabbit polyclonal anti-MOR is known to be directed against the amino acids 386-398 of the MOR [4] and also known to recognize an expected protein band at 55 kDa in Western blot analysis of MOR transfected HEK293 cells [33] and mouse brain tissue [34].…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the subunits of skeletal muscle L-type calcium channel are not expressed simultaneously during differentiation of myotubes in vitro. We have shown that the α2δ1 subunit is the first one to be expressed in freshly dissociated satellite cells and is followed by expression of the α1, β, and γ subunits [6,7]. Further, we have shown that more than 50 % of freshly isolated satellite cells express α2δ1 subunit and that these cells commit to the muscle lineage to form myotubes [7].…”
Section: Introductionmentioning
confidence: 92%